The modifiability of cognitive style and its relationship to achievement in biology - Prime, Glenda M. (1988)
This study examines the nature of the relationship between breadth of categorization and biology achievement for secondary school biology students, as well as the extent to which this cognitive style could be modified by instruction. The sample consisted of two intact fourth-form biology classes at St. George's College, Trinidad--one serving as the experimental group and the other as the control group. The treatment was a researcher-designed unit of instruction in broad categorizing. Analysis of the data revealed that for females in the sample, a positive correlation between biology achievement and broad categorizing was obtained when IQ was controlled. It also revealed a significant treatment effect as evidenced by breadth of categorization scores for an experimental group
Keywords: Secondary school students